Digital humanistic program to manage premature frailty in young breast cancer survivors with gender perspective - Yun Hu; Joshua Wiley; Lulu Jiang; Xiyi Wang; Ran Yi; Jiehui Xu; Yanyan Liu; Aozhou Weng; Futai Zou; Eun-Ok Im (npj Digital Medicine)
Abstract Premature frailty is a critical challenge for young breast cancer survivors (YBCSs), impacting their health and perpetuating gender inequality through heightened vulnerability and marginalization. While digital health shows promise in frailty screening, its effectiveness for comprehensively managing frailty remains inconclusive. This randomized controlled trial, registered at the Chinese Clinical Trial Registry (ChiCTR2200058823), tests the “AI-TA” program’s efficacy on premature frailty and quality of life in YBCSs. The intervention group received a gender- and generation-sensitive program combining artificial intelligence interactions and humanities skills. The control group received 12 weeks of online information support. Both groups improved in frailty dimensions (P < 0.05); the intervention group showed notable enhancements in psychological (P = 0.013) and social frailty (P < 0.001). Quality of life also improved more in the intervention group from T1 to T2 (β = 15.384, 95% CI:13.028–17.740, P < 0.001). Results show a gender- and generation-sensitive digital humanistic program can optimize frailty management, promoting survivorship and gender equity.